Analysis of Head Nurse on Transformational Leadership and Patients Safety Culture in Palang Merah Indonesia (PMI) Hospital at Bogor, Indonesia - Dwi Setiowati (International Journal of Nursing and Health Services (IJNHS), 2020)
A head nurse transformational leadership is one of the factors that play a role in the successful implementation of a patient safety culture. The previous study found that the implementation of patient safety culture in PMI Bogor Hospital was not optimal. There was a relationship between the transformational leadership of the head nurse and the application of patient safety culture by the nursing nurse at PMI Bogor Hospital. This is entirely meaningful primary data for the researcher to conduct follow-up research. The research method was a quantitative approach collecting a sample of 30 head nurse in the PMI Bogor hospital. The data analysis used Chi-Square. The results showed that the head nurse transformational leadership toward the patient safety culture in PMI Bogor hospitals were mostly good. The application of a patient safety culture at the hospital of PMI Bogor were Mostly were not good. There is a mentoring relationship between the head nurse transformational leadership in the application of a patient safety culture at the PMI Bogor hospital. A Good head nurse transformational leadership will have a 6.2 times chance to implement a good safety culture. It needs an awareness of the head as a first-line nursing manager in improving knowledge and transformational leadership skills supported by the Director of the Hospital and the field of nursing through sustainable mentoring/in house training